2019
DOI: 10.1089/ast.2018.1889
|View full text |Cite
|
Sign up to set email alerts
|

Mosses in Low Earth Orbit: Implications for the Limits of Life and the Habitability of Mars

Abstract: As a part of the European Space Agency mission ''EXPOSE-R2'' on the International Space Station (ISS), the BIOMEX (BIOlogy and Mars EXperiment) investigates the habitability of Mars and the limits of life. In preparation for the mission, experimental verification tests and scientific verification tests simulating different combinations of abiotic space and Mars-like conditions were performed to analyze the resistance of a range of model organisms. The simulated abiotic space-and Mars-stressors were extreme tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…With regard to the EVTs and SVTs, we present the results obtained by analysis of the fungus Cryomyces antarcticus (Pacelli et al, 2019) and the moss Grimmia sp. (Huwe et al, 2019). Results obtained after space exposure are shown from a series of analyses on the biofilm kombucha (Podolich et al, 2019), the cyanobacterium Chroococcidiopsis (Billi et al, 2019), the cryptoendolithic Antarctic fungus Cryomyces antarcticus (Onofri et al, 2019), and the lichens Buellia frigida (Backhaus et al , this issue) and Circinaria gyrosa (de la Torre et al , not part of this issue).…”
Section: Overview Of Results Within This Special Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the EVTs and SVTs, we present the results obtained by analysis of the fungus Cryomyces antarcticus (Pacelli et al, 2019) and the moss Grimmia sp. (Huwe et al, 2019). Results obtained after space exposure are shown from a series of analyses on the biofilm kombucha (Podolich et al, 2019), the cyanobacterium Chroococcidiopsis (Billi et al, 2019), the cryptoendolithic Antarctic fungus Cryomyces antarcticus (Onofri et al, 2019), and the lichens Buellia frigida (Backhaus et al , this issue) and Circinaria gyrosa (de la Torre et al , not part of this issue).…”
Section: Overview Of Results Within This Special Collectionmentioning
confidence: 99%
“…The bryophyte Grimmia sp. was an exception (Huwe et al, 2019), but further analysis after space exposure might show whether this specific moss is also resistant to the conditions in space. Actual results in reference to the bryophytes were shown only for the preflight selection mode of EVT and SVT.…”
Section: Overview Of Results Within This Special Collectionmentioning
confidence: 99%
“…Exposure to temperature ranges of -25 to 60 • C had no effect on the samples. This exposure was short-term, and these effects might be different when bryophytes are exposed to the same temperatures for longer periods of time [174]. These results showed that bryophytes have a high potential for survival in Martian conditions, although more research is needed.…”
Section: Bryophytesmentioning
confidence: 94%
“…Bryophytes are considered pioneers among plants due to their habitation of very dry environments [173]. Research on the limits and survivability of bryophytes under simulated Martian and space conditions were assessed recently for the first time by Huwe et al [174] as a part of the complex experiment BIOMEX (Biology and Mars Experiment), outside the International Space Station [175]. Bryophytes of the genus Grimmia were collected from an alpine environment from the Swiss Alps and exposed to simulated Martian conditions (Mars atmosphere gas mixture, 370 ppm H 2 O, 1 kPa for 31 days with 17-day or without (control) exposure to UV 200-400 nm radiation for a total dose of 5 × 10 5 kJ/m 2 ).…”
Section: Bryophytesmentioning
confidence: 99%
“…Huwe et al (2019) report limited exposure of Grimmia species to Mars-like atmospheres did not affect photosynthetic activity, noting many Grimmia species occur in cold altitudes (to 5000 m a.s.l. ), on basalt or granite, hair points providing protection against UV and desiccating wind.…”
mentioning
confidence: 88%